KELISANAN DAN KEBERAKSARAAN DALAM SITI SURABAYA KARYA F AZIZ MANNA - Dheny Jatmiko; Endang Poerbowati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2015)
Abstract. This article analyzed the poem F. Aziz Mannaâ€™s "Surabaya Siti" from two perspectives, namely the oral culture and written culture. "Siti Surabaya" was one of the poems in the collection of poems Siti Surabaya dan Kisah Para Pendatang. The poem was a product of the written cultural community exploring on oral culture. The analysis showed that from the perspective of oral culture "Siti Surabaya" was a poem that exploited the spoken characteristics. These characteristics were used as the motor of poetry aesthetic. However, from the perspective of literacy culture, the representation of I-lyric in "Siti Surabaya", could be understood as a woman, a town, and the representation of Surabaya.Â Keyword: kelisanan, keberaksaraan, surabaya Â